A Critique of Aldo Leopold Land Ethic for Environmental Management - Maxwell-Borjor Achuk Eba (Universitas Negeri Makassar, 2020)
There is no question of doubt that Aldo Leopold (1887-1948) is regarded as the most influential figure in the development of an economic environmental ethics. The cornerstone of his environmental ethics is science. In fact, the science of ecology in the real sense of the term was developed during his life time and it would not be an exaggeration to say that he was the first person to call for a radical rethink of ethics in the light of science. In his collective essays published posthumously as A Sand Country Almanac (1949), the essay ‘Land Ethic’ included in this book is the systematic presentation of an eco-centric ethics. This work attempt to critique Aldo Leopold Land ethics for environmental management. This work applauds Aldo Leopold ‘land ethic’ because he sees the ecosystem as an organic wholes and its values implicit in concepts such as integrity and stability, health and well-being. However, this work criticized Aldo Leopold ‘Land Ethics’ because his view of organic model of ecological systems is inadequate. This is because of the fact that species within an ecosystem could exist outside the organism. Thus, Aldo Leopold ‘land ethic’ is not holistic enough.